Children’s contact with police as a victim, person of interest and witness in New South Wales, Australia - Whitten, Tyson (The Australian and New Zealand journal of criminology, 2020)
Contact with the police, as the first contact with the criminal justice system for young people and children, may signify individuals who are vulnerable to later adverse social and health outcomes. However, little is known about how often children have contact with police or for what reason. In this paper, we provide a demographic profile of the prevalence and reasons for police contact among a representative, longitudinal, population-based sample of 91,631 young people in New South Wales, Australia. By 13 years of age, almost one in six (15.6%) children had contact with police as a victim, person of interest and/or witness on at least one occasion. The most common reason for contact with police was in relation to an assault. There was considerable overlap among children who had been in contact with police on more than one occasion for different reasons, with those having police contact as a person of interest or witness being seven times more likely to have also been in contact with police as a victim in a separate incident, than children not known to police. We show that contact with the police is surprisingly common among children and suggest that early interventions for children in contact with police might prevent a range of adverse outcomes not limited to criminal offending.